Rheumatoid arthritis unmasked: the immune complex as a key driver of disease progression - Veshalini Kasiraja; Noor Azlina Abu Bakar; Noor Azuin Suliman (Exploration of Immunology)
Rheumatoid arthritis (RA) is an inflammatory autoimmune disorder characterised by synovial joint destruction and systemic complications. Central to its pathogenesis is the formation and deposition of immune complexes (ICs), which result from antigen-antibody interactions involving autoantibodies such as rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPAs). These ICs infiltrate joint tissues, activate the complement system, and initiate a cascade of inflammatory responses. The ensuing recruitment of polymorphonuclear leukocytes and release of pro-inflammatory cytokines and chemokines contribute to sustained inflammation, tissue degradation, and joint deformity. RA is thus classified as a type III hypersensitivity disorder, wherein IC-mediated mechanisms perpetuate a self-amplifying inflammatory loop. This review explores the evolving understanding of IC-driven pathophysiology in RA, emphasising the three-stage progression of IC formation, deposition, and inflammatory activation. By elucidating the interplay between hypersensitivity reactions and immune-mediated mechanisms in RA, the review underscores potential therapeutic targets that may help disrupt this pathogenic cycle. Enhanced comprehension of IC dynamics not only deepens insight into RA progression but also opens avenues for more precise and effective interventions in autoimmune diseases.